2005
DOI: 10.1002/bit.20365
|View full text |Cite
|
Sign up to set email alerts
|

Dual substrate biodegradation of a nonionic surfactant and pentachlorophenol by Sphingomonas chlorophenolica RA2

Abstract: The simultaneous biodegradation of the nonionic surfactant Tween 20 (Tw20) and pentachlorophenol (PCP) by Sphingomonas chlorophenolica sp. Strain RA2 (RA2) was measured. As a sole substrate, Tw20 biodegradation was best described by the Contois kinetic model. During concurrent biodegradation of Tw20 and PCP, the biodegradation rates of Tw20 were not significantly affected by 50 or 100 mg/L PCP, but were significantly inhibited by 500 mg/L PCP. Decreases in cell yield in the presence of PCP suggest that PCP was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In addition to endogeneous metabolism, the utilization of dual substrates, glucose, and peptone, as complementary substrates was considered in the Model 3. Although the assumption that only one mostlimiting substrate presents during microbial growth holds for many cases, several studies on microorganisms that are simultaneously limited by two or more substrates have been reported (Bielefeldt and Cort, 2005;Machado and Grady, 1989;Neeleman et al, 2001;Lee et al, 1984;Sambanis et al, 1986;Yoon et al, 1977). In this study, the Model 3, dualsubstrate steady-state model, was demonstrated to be superior than the Model 2 in predicting biomass concentration, especially at D < 0.25/h when consumption of peptone and release of ammonia became substantial.…”
Section: Significance Of the Dual-substrate Steady-state Modelmentioning
confidence: 59%
“…In addition to endogeneous metabolism, the utilization of dual substrates, glucose, and peptone, as complementary substrates was considered in the Model 3. Although the assumption that only one mostlimiting substrate presents during microbial growth holds for many cases, several studies on microorganisms that are simultaneously limited by two or more substrates have been reported (Bielefeldt and Cort, 2005;Machado and Grady, 1989;Neeleman et al, 2001;Lee et al, 1984;Sambanis et al, 1986;Yoon et al, 1977). In this study, the Model 3, dualsubstrate steady-state model, was demonstrated to be superior than the Model 2 in predicting biomass concentration, especially at D < 0.25/h when consumption of peptone and release of ammonia became substantial.…”
Section: Significance Of the Dual-substrate Steady-state Modelmentioning
confidence: 59%
“…[1][2][3] One of the longest and best characterized bacterial aromatic catabolic pathways involves the degradation of 4-hydroxyphenylacetic acid (4-HPA) via 3,4-dihydroxyphenylacetic acid (homoprotocatechuate, HPC) to pyruvate and succinic semialdehyde. 4 This Escherichia coli pathway has similarities to the catechol (TOL) meta fission pathway of Pseudomonads.…”
Section: Introductionmentioning
confidence: 99%
“…This led to the microbial utilization of the non‐ionic surfactant as a carbon or energy source being accelerated. Bielefeldt and Cort found the same phenomenon for pentachlorophenol and non‐ionic surfactant (Tween 20) biodegradation 36. Pentachlorophenol was acting as an uncoupler and allowed the bacteria to utilize Tween 20 during biodegradation.…”
Section: Resultsmentioning
confidence: 71%